Pradėtas vykdyti naujas Lietuvos mokslo tarybos finansuojamas mokslinių grupių projektas "Eozinofilų įtaka bronchų lygiųjų raumenų remodeliacijai sergant astma" - Kalinauskaitė, Virginija; Malakauskas, Kęstutis (Pulmonologija ir alergologija, 2014)
Asthma is a common chronic inflammatory disease of the airways characterized by variable and recurring symptoms, reversible airflow obstruction and bronchospasm. Structural changes reported in the airways of asthmatics include epithelial fragility, goblet cell hyperplasia, angiogenesis, increased extracellular matrix protein secretion, increased airway smooth muscle mass, wall thickening. Airway smooth muscle (ASM) cells and eosinophils actively participate in airway remodelling. Despite the widely recognized importance of eosinophils in the pathogenesis of asthma and their influence on bronchial smooth muscle remodeling is not well understood. The research group from Department of Pulmonology and Immunology, Lithuanian University of Health Sciences in collaboration with the Department of Molecular Pharmacology, University of Groningen since March 2014 launched by Research Council of Lithuania funded researcher team‘s project “Eosinophil induced airway smooth muscle remodelling in asthma” (financing contract no. MIP-010/2014) in order to carry out detailed studies of airway remodeling.